A General Equilibrium Analysis of the TPP Free Trade Agreement With and Without China. (May 2014) - Xin, Li
The approaching tenth year of the Doha Round with no achievements to celebrate indicates a failure of the World Trade Organization. Formal negotiations of the Round expired in 2005 without reaching a consensus, and informal negotiations were stalled in 2008. Thus, the Trans-Pacific Partnership (TPP), a recent initiative to deepen trade relations among countries bordering the Pacific, was greeted with applause and relief as a step in the right direction. This article discusses the region-wide Free Trade Agreement series of linked agreements that cover various members and issues. The recursive dynamic computable general equilibrium (CGE) model simulates two scenarios against the baseline, namely, a TPP agreement with China and without China. The preliminary results show that the TPP agreement without China cannot change the significant roles of markets and geography as the principal factors behind the economic integration of Southeast Asia with China. Trade and investment agreements facilitate market forces, they do not oppose them. The integration of the Asia–Pacific countries may benefit the US and other key economies. JEL Classification: F12, F14, F15